Volumetric analysis of pharyngeal airway dimensions and hyoid bone position following orthognathic surgery in skeletal class III patients: a cross sectional cephalometric study - Thapa, Amrit; Roy, I. D.; Jayan, B.; Ray, Saugat; Kumar, Andrews Navin; Antil, Amit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Objective of the study was to determine linear and volumetric changes in pharyngeal airway dimensions in class III patients treated by different modalities of orthognathic surgery and to compare the results of different orthognathic surgical modalities, and determine the change at the position of the hyoid bone. Methods: Pre and post-treatment lateral cephalogram of 53 class III adult patients who were treated by different modalities of orthognathic surgery studied to assess the changes in pharyngeal airway dimensions and hyoid bone position after orthognathic surgery. 28 patients were treated with mandibular set back, and 25 patients were treated with Bijaw surgery. Lateral cephalogram records were taken before treatment (T1), after surgery (T2), the end of the fixed treatment (T3) and 1 year after debonding (T4). Results: Interception of both surgical modalities has significant impact on various skeletal and pharyngeal parameters i.e., BMeH (0.00), PNS (0.009), MPS (0.13), GOP (0.001), IPS (0.007), SAS (0.006), and MAS (0.00). OJ (overjet) and OB (overbite) was significant especially after time interval of one year. In Bijaw groups, PPST4 parameter was significantly increased (0.0000), SPST4 (0.000), GOP (0.000), EPS (0.000) and IPS parameter was significantly decreased (0.045). Significant difference was observed in T4 time interval in superior pharyngeal airway space, posterior airway space and middle airway space with (p<0.05). Conclusions: Pharyngeal airway is significantly altered following orthognathic surgery in class III patients and it depends on the type of surgical modality employed were Bijaw surgery has significant impact on oropharyngeal and hypopharyngeal airway space.